Neural Consequences of Chronic Short Sleep: Reversible or Lasting? - Zhao, Zhengqing; Zhao, Xiangxiang; Veasey, Sigrid C. (Frontiers in Neurology, 2017)
Approximately one third of adolescents and adults in developed countries regularly experience insufficient sleep across the school and/or work week interspersed with weekend catch up sleep. This common practice of weekend recovery sleep reduces subjective sleepiness, yet recent studies demonstrate that one weekend of recovery sleep may not be sufficient in all persons to fully reverse all neurobehavioral impairments observed with chronic sleep loss, particularly vigilance. Moreover, recent studies in animal models demonstrate persistent injury to and loss of specific neuron types in response to chronic short sleep with lasting effects on sleep/wake patterns. Here we provide a comprehensive review of the effects of chronic sleep disruption on neurobehavioral performance and injury to neurons, astrocytes, microglia and oligodendrocytes and discuss what is known and what is not yet established for reversibility of neural injury. Recent neurobehavioral findings in humans are integrated with animal model research examining long-term consequences of sleep loss on neurobehavioral performance, brain development, neurogenesis, neurodegeneration, and connectivity. What is known of the molecular mechanisms underlying sleep loss neural injury will be described and future directions for work in this emerging area of sleep neurobiology will be discussed.While it is now clear that recovery of vigilance following short sleep requires longer than one weekend, less is know of the impact of chronic short sleep on cognitive function, mood and brain health long term. From work performed in animal models chronic short sleep in the young adult and short term sleep loss in critical developmental windows can have lasting detrimental effects on neurobehavioral performance.